1997
DOI: 10.1046/j.1365-3024.1997.d01-141.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological reactivity to heat shock protein 70 in patients with hydatid disease

Abstract: Heat shock protein 70 (hsp70) was chosen as a model antigen with which to investigate autoantibody production in humans with cystic hydatid disease. Levels of specific serum antibody were assessed in the sera of patients with surgically confirmed infection with E. granulosus and sera from non-infected controls. Antigens used were human hsp70, obtained from K562 cells grown in culture, and E. granulosus hsp70 obtained by expression of the full length protein in Escherichia coli following cloning of the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…Infection, especially chronic infection, might therefore be expected to induce antibodies to both the HSP70 of the infectious agent and to self‐HSP70. Nevertheless, with the exception of Plasmodium falciparum malaria, in which antibodies to human HSP70 were detected in 48 of 62 sera (77%) from Brazilian patients, 17 such autoantibodies are usually found in lesser frequency in infected individuals 15,18 . In the present study, sera from only 12 of 52 patients with IPBSNHL (23%) reacted with rhHSP70.…”
Section: Discussioncontrasting
confidence: 49%
“…Infection, especially chronic infection, might therefore be expected to induce antibodies to both the HSP70 of the infectious agent and to self‐HSP70. Nevertheless, with the exception of Plasmodium falciparum malaria, in which antibodies to human HSP70 were detected in 48 of 62 sera (77%) from Brazilian patients, 17 such autoantibodies are usually found in lesser frequency in infected individuals 15,18 . In the present study, sera from only 12 of 52 patients with IPBSNHL (23%) reacted with rhHSP70.…”
Section: Discussioncontrasting
confidence: 49%
“…Using an enzyme‐linked immunosorbent assay (ELISA) in which recombinant HSP70 of Leishmania donovani origin was used as antigen, Arora et al 49 found anti‐HSP70 antibodies in 22 of 26 (85%) of patients with SLE and 12 of 20 (60%) of control serum sample. In another ELISA‐based study, employing recombinant Echinococcus granulosus HSP70, antibodies were detected in 60% of serum samples from hydatid patients and 21% of samples from healthy controls 50 ; the level of reactivity was significantly higher in hydatid patients. In the present study, we were unable to distinguish reactive control from reactive patient serum by serial dilution (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…1993, Ersfeld & Craig 1995, Martin et al . 1996, Colebrook & Lightowlers 1997). We have recently isolated an elongation factor‐1β/δ from a cDNA library of E. granulosus and have investigated its role in the host–parasite relationship.…”
Section: Introductionmentioning
confidence: 99%